Assessing LLIN distribution implementation using evidence-informed intervention core elements: a qualitative study in a resource constrained setting - Dako‑Gyeke, P.; Asampong, E.; Glozah, F.N.; et al. (BMC Health Services Research, 2024)
Background The National Malaria Elimination Programme implements the mass LLIN Distribution Campaigns in Ghana. Implementation science promotes the systematic study of social contexts, individual experiences, real-world environments, partnerships, and stakeholder consultations regarding the implementation of evidence-informed inter‑ ventions. In this paper, we assess the core elements of the mass LLIN distribution campaign in a resource constrained setting to learn best implementation practices. Three core domains were assessed through the application of Gal‑ braith’s taxonomy (i.e., implementation, content, and pedagogy) for evidence-informed intervention implementation. Methods Six districts in two regions (Eastern and Volta) in Ghana participated in this study. Fourteen Focus Group Discussions (FGDs) were conducted across these communities. Eligible participants were purposively sampled considering age, occupation, gender, and care giving for children under 5 years and household head roles. All audio-recorded FGDs were transcribed verbatim, data was assessed and coded through deductive and inductive processes. NVivo software version 13 was used for the coding process. Themes were refned, legitimized, and the most compel‑ ling extracts selected to produce the results. Results Sixty-nine (69) caregivers of children under 5 years and sixty (60) household heads participated in the FGDs. All caregivers were females (69), whilst household heads included more males (41). Core elements identifed under implementation domain of the LLIN distribution campaign in Ghana include the registration and distribu‑ tion processes, preceded by engagement with traditional authorities and continuous involvement of community health volunteers during implementation. For pedagogy domain, core elements include delivery of intervention through outreaches, illustrations, demonstrations, and the use of multiple communication channels. Core elements realized within the content domain include information on effective malaria prevention, and provision of information to enhance their self-efficacy. Yet, participants noted gaps (e.g., misuse) in the desired behavioural outcome of LLIN use and a heavy campaign focus on women. Conclusion and recommendations Although the implementation of the mass LLIN distribution campaigns exhibits components of core elements of evidence-informed interventions (implementation, content and pedagogy), it has not achieved its desired behavioural change intentions (i.e. continuous LLIN use). Future campaigns may consider use of continuous innovative pedagogical approaches at the community level and lessons learnt from this study to strengthen the implementation process of evidence-based health interventions. There is also the need for stand‑ ardization of core elements to identify the number of core elements required within each domain to achieve efficiency
Research Article
Keywords: Long lasting insecticide treated nets (LLIN); Evidence informed interventions; Core elements